Optimization of Cashew Gel (Anacardium Occidentale L) In The Wound Treatment In Mice (Mus Muscullus) Test Animal - Sahuri Teguh Kurniawan; Azhari Arum Pramesti; Noerma Shovie Rizqiea (Universitas Muhammadiyah Semarang, 2026)
A wound is a condition where the structure and function of the skin are damaged. Wounds on the skin often appear in daily life and are considered trivial, although the injuries that occur tend to be minor but require immediate treatment. Cashew (Anacardium occidentale L.) contains saponins, tannins, alkaloids, flavonoids, and ascorbic acid, which can accelerate the wound healing process during treatment. This research aimed to identify the effect of cashew gel (Anacardium occidentale L.) in the wound treatment of test animals (mice, Mus musculus). This research used a true experiment method with a post-test-only control group design in the Integrated Laboratory at Kusuma Husada University of Surakarta. This research used 18 mice as test animals, divided into three groups: an intervention group with cashew extract gel (200 mg), an intervention group with cashew extract gel (300 mg), and a negative intervention group with NaCl (0.9%). An incision wound with a length of 10.00 mm was made using a scalpel, number 11. The parameters observed were wound size, wound healing time, and healing percentage. The data was analyzed using the one-way ANOVA test. The research results showed that cashew extract gel 300 mg had a wound healing percentage of 51.91%, and the wound treatment process was better than the other intervention groups. Based on the one-way ANOVA test, a significant result with a p-value of 0.005 < 0.05 was obtained. It can be concluded that cashew gel (Anacardium occidentale L.) has an effect on the wound treatment in mice (Mus musculus) test animals.